2016
DOI: 10.15232/pas.2016-01510
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical linkage of total-tract digestion of starch and neutral detergent fiber to their fecal concentrations and the effect of site of starch digestion on extent of digestion and energetic efficiency of cattle

Abstract: Published regression equations relating digestibility of starch to fecal starch concentration have slopes that differ by over 5-fold. Hence, nutritionists have questioned their legitimacy. Total-tract starch digestibility and concentration of starch in feces are interlocked mathematically by 2 factors-starch content of the diet and digestibility of diet DM. Digestibility data compiled from the published literature including 201 diets fed to lactating dairy cows and 191 diets fed to feedlot cattle were employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 31 publications
(37 reference statements)
3
35
0
Order By: Relevance
“…Validation of the calibration included not only samples from the current study but also from other feedlot studies as described in Jancewicz et al (2017a). Fecal starch, NDF, and ADL were selected as the key nutrients of interest based on results from regression models (described below) and previous studies (Jancewicz et al 2017b;Owens et al 2016). Reference analysis consisting of wet chemistry for OM, starch, N, NDF, ADF, ADL, and EE (AOAC 2005) was conducted on a subset of fecal samples from each feedlot (24 from the current study) and the samples of which neighborhood distance (ND) was above a certain threshold (0.60) were used to expand the original calibration.…”
Section: Analysis Using Nirsmentioning
confidence: 99%
See 2 more Smart Citations
“…Validation of the calibration included not only samples from the current study but also from other feedlot studies as described in Jancewicz et al (2017a). Fecal starch, NDF, and ADL were selected as the key nutrients of interest based on results from regression models (described below) and previous studies (Jancewicz et al 2017b;Owens et al 2016). Reference analysis consisting of wet chemistry for OM, starch, N, NDF, ADF, ADL, and EE (AOAC 2005) was conducted on a subset of fecal samples from each feedlot (24 from the current study) and the samples of which neighborhood distance (ND) was above a certain threshold (0.60) were used to expand the original calibration.…”
Section: Analysis Using Nirsmentioning
confidence: 99%
“…Cereal grains are a major ingredient in diets for finishing cattle, and given the high proportion of starch in grains, predictions have been developed to rapidly estimate starch digestibility using fecal starch concentration (Zinn et al 2002;Corona et al 2005;Zinn et al 2007). Research by Owens and Zinn has shown that the accuracy of starch digestibility predictions can be improved by including additional variables such as fecal N (Zinn et al 2011), dry matter (DM) or organic matter (OM) digestibility, and starch intake (Owens et al 2016). Methods to predict other nutrient digestibilities, particularly neutral detergent fiber (NDF), from their fecal concentrations have been examined (Fredin et al 2014;Jancewicz et al 2016;Owens et al 2016), as well as indirect relationships between OM digestibility and fecal crude protein (CP) (Lukas et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Owens et al (2016), when evaluating published regression equations, concluded that the relationship of starch digestibility and fecal starch must be curvilinear, not linear. According to the authors, although these two variables are mathematically linked, additional factors are essential for an accurate relationship: (a) daily fecal output, which varies with the indigestibility of dietary DM; and (b) starch intake, which varies with its dietary concentration and dry matter intake.…”
Section: Discussionmentioning
confidence: 99%
“…for starch digested in the rumen, small intestine, and large intestine as estimated by Huntington et al (2006), the point and extent to which efficiency of use of energy from digested starch can be calculated as outlined by Owens et al (2016).…”
Section: Discussionmentioning
confidence: 99%